The Effect of Siamese Oranges on Distress, Pulse, Blood Pressure - Tajudin, Tajudin; Husnayanti, Ana; Siburian, Christine Handayani; Chaerani, Erni (Jurnal Keperawatan Priority, 2025)
Distress is one of the daily psychological complaints of modern society that cannot be avoided. Distress can attack students who are in the learning process, especially first-year students. The level of distress in first-year students is relatively high due to adjustment to the new environment, lack of adaptability and many demands that must be done such as completing assignments. High distress can be reduced by giving aromatherapy. One of them is aromatherapy produced by Siamese oranges. Siamese oranges have many benefits, one of which is obtained from their skin which can emit aromatherapy that can provide a sense of calm and relieve anxiety. The aim was to determine the effect of siamese oranges on distress, pulse, blood pressure in Level 1 Nursing Students of Health Polytechnic of Pangkal Pinang. The research design used was a quasi-experimental one group pretest and posttest. The sample was 74 people with a total sampling technique. The variables were Distress with the Kessler Psychological Distress Scale, Pulse and BP. This study showed that before the intervention the average distress was 3.5, pulse 81.43 times/minute, SBP 109 mmHg, DBP 75.47 mmHg and after the intervention the average distress was 2.16, pulse 83.07, SBP 106.49 mmHg, and DBP 73.38 mmHg and there was an effect of tangerine on distress (0.000), pulse (0,043), and BP (0,000) in Level 1 students of the Ministry of Health Polytechnic of Pangkal Pinang. Tangerine produces aromatherapy that can affect the reduction of distress, pulse and blood pressure.